Pelatihan Pengelasan dan Inspeksi kepada Siswa SMAN 3 Sampang sebagai Upaya Penguatan Indeks Pembangunan Manusia (IPM) - Arief Syarifuddin; Aurista M. Ilmah; Taufan Prasetyo; Desta Rifky Aldara; Mohammad Abdullah (I-Com: Indonesian Community Journal, 2024)
Madura Island is part of the province of East Java which has a lot of potential, starting from tourism, natural resource potential, such as oil, natural gas, and salt, as well as cultural potential. Until now, the large potential possessed by the island of Madura has not been managed optimally; this is partly due to the low interest of the Madurese people in studying as much as possible. Welding and inspection training for SMAN 3 Sampang students as an effort to strengthen the Human Development Index (HDI) in the sector of improving the quality of human resources is one of the efforts that will be taken by the Maritime Technology Department of the Madura State Polytechnic to be able to improve the quality of high school graduates. Hence, they are ready to compete in the world of work. Overall, the training resulted in a good understanding for participants, as evidenced by the improvement in post-test results. The training participant satisfaction questionnaire showed poor and poor results for several aspects of resource persons, training materials, and consumption.